“desarrollo e implementación de una herramienta informática para reducir costos operativos en la etapa de perforación y voladura en labores subterráneas de la empresa constructores mineros los andes sac –marsa–” - De La Cruz Terrones, Robinson Anderson (2016)
This project aims to develop and implement a software tool that is based o mathematical models, with which the optimum mesh design drilling / blasting conventional, such as cut and galleries in the mining company MARSA underground work is carried out. To develop the improvement and optimization of the mesh drilling / blasting in mining MARSA, it has been used mathematical models and algorithms for making such software tool which is adaptable to the diverse and varied characteristics of the rock mass at once is management simple, practical, fast and insituo, it involves running an investigation involving the maximum number of variables and geomechanical conditions. Tests done were done in a nonrandom sample and were CR .10963-S, GAL 963-S, GAL. 963-N, located in the area of Valeria II, work carried out by specialized contract manufacturers miners los Andes SAC . The results presented corroborate the applicability of this tool, 15 shots were fired, 5 in each work, and it resulted that 96% of them were satisfactory and only 4% were blown shots caused by problems with the initiation, mooring etc., but these contingencies are gradually overcoming anger go as implemented in the new mining unit drilling mesh design. We conclude that it is a software tool with wide applicability, versatility and easy operation, which is the starting point to develop and implement an optimal and suitable mesh design drilling mining MARSA, to optimize the distribution of the explosive charge and therefore energy efficiency in advance by firing is improved, reducing operational costs involved in the process of drilling and blasting.